Redesain Dermaga Kawasan Tepi Air Sungai Mahakam - Azizah, Anisah; Sari, Dharwati P.; Destiono, Wahyudi Bintang (TRANSFORM: Journal of Tropical Architecture and Sustainable Urban Science, 2025)
This study explores the planning of a waterfront area along the Mahakam River, focusing on the Sungai Kunjang Dock in Samarinda City. The Mahakam River plays a vital role as a transportation route and economic artery for the surrounding community. However, the infrastructure of the river port—particularly the dock—remains suboptimal in terms of functionality, aesthetics, and public comfort. A descriptive qualitative method was employed, supported by field observation, literature review, documentation, and SWOT analysis. The findings reveal that the port area holds significant potential to be developed as a multifunctional public space through a waterfront development approach. The proposed design applies principles of ecological and social integration by incorporating green open spaces, indoor gardens, children’s playgrounds, exhibition spaces, and supporting facilities. The design concept, named “SENARA,” emphasizes the harmonious relationship between humans and the river as a core urban identity. This redevelopment is expected to enhance the environmental quality of the waterfront while strengthening the port’s social, economic, and tourism functions in a sustainable manner.